Grounding human-object interaction to affordance behavior in multimodal datasets - Henlein, Alexander; Gopinath, Anju; Krishnaswamy, Nikhil; Mehler, Alexander; Pustejovsky, James (Frontiers in Artificial Intelligence, 2023)
While affordance detection and Human-Object interaction (HOI) detection tasks are related, the theoretical foundation of affordances makes it clear that the two are distinct. In particular, researchers in affordances make distinctions between J.J. Gibson’s traditional definition of an affordance, “the action possibilities” of the object within the environment, and the definition of a telic affordance (Pustejovsky, 2013), or one defined by conventionalized purpose or use. We augment the HICO-DET dataset with annotations for Gibsonian and telic affordances and a subset of the dataset with annotations for the orientation of the humans and objects involved. We then train an adapted Human-Object Interaction (HOI) model and evaluate a pre-trained viewpoint estimation system on this augmented dataset. Our model, AffordanceUPT, is based on a two-stage adaptation of the Unary-Pairwise Transformer (UPT), which we modularize to make affordance detection independent of object detection. Our approach exhibits generalization to new objects and actions, can effectively make the Gibsonian/telic distinction, and shows that this distinction is correlated with features in the data that are not captured by the HOI annotations of the HICO-DET dataset.